On the description of the consolidation phenomenon by means of a two-component continuum - Kempa, W. (Archives of Mechanics, 1997)
The purpose of the present paper is the consistent formulation of the initial-boundary value problem for the consolidation phenomenon within the frame of a new two-component continuum model. The new class of models of two-component continua characterized by the balance equation for porosity is presented. The initial-boundary value problem with regard to the physical features of the consolidation is formulated. Some additional constitutive relations for the boundary quantities are proposed. Bearing in mind these constitutive relations, an example of a one-dimensional structure is calculated. The results of the numerical simulation are the basis for the parameter study of some constants of the model.